Computer networks and information technologies second international conference on advances in communication, network, and computing, CNC 2011, Bangalore, India, March 10-11, 2011. proceedings - Das, Vinu V.; Stephen, Janahanlal; Chaba, Yogesh (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Advances in Communication, Network, and Computing, CNC 2011, held in Bangalore, India, in March 2011. The 41 revised full papers, presented together with 50 short papers and 39 poster papers, were carefully reviewed and selected for inclusion in the book. The papers feature current research in the field of Information Technology, Networks, Computational Engineering, Computer and Telecommunication Technology, ranging from theoretical and methodological issues to advanced applications.